Perancangan Company Profile Sebagai Media Informasi Visual Pada Kelompok UMKM Desa Lampoko Kec. Balusu Kab. Barru - Indah, A. Besse Riyani; Rusman, Muhammad; Hanafi, Rosmalina; Mardin, Farid; Tahir, Nurfaidah; Handayani, Dwi; Calista, Dea; Ikhsan, Triananda Shafira; Rum, Muhammad Fadel; Nursaid, Muhammad (Faculty of Engineering UNHAS, 2023)
MSMEs are one of the drivers of the economy in Indonesia that can increase people's productivity. However, the problem that most MSMEs experience is in marketing their products. It is still difficult for MSMEs to carry out marketing because they have not maximized visual information media in carrying out marketing activities and expanding networking. This also happened to MSMEs assisted by Lampoko Village, Barru Regency. Several coached MSMEs have not maximized visual information media in carrying out marketing and networking activities. Company profile is a form of visual information media that can be applied to MSMEs so that the business profile of MSMEs can be known and support increased sales. In this service activity, a company profile was designed for the MSME Group assisted by Lampoko Village. The Company Profile is designed to support marketing activities and expand the networking of each MSME. From the results of service activities based on measuring activity achievements, it shows that on average MSMEs understand the function of the company profile and understand the content in it and know how to use the company profile for marketing activities and expanding networking.